Actualizing the Business English Course by Using an E-Commerce Platform - Soraya Grabiella Dinamika; Elitaria Bestri Agustina Siregar (Journal of English Language Teaching and Linguistics, 2022)
The rapid development of digital technology has become a trigger for educators to create and demonstrate up-to-date yet flexible learning methods. Educators are challenged to integrate lessons with the medium of available technology. In this study, the researcher encourages students to engage in real business (buying and selling) activities by utilizing electronic commerce (e-commerce) platform to actualize the purpose of the Business English course. The descriptive qualitative method used employs questionnaires for data collection. The objectives of this study are: to find out the role of e-commerce platforms in Business English learning and the student’s course achievement. Since this learning integration is experiential to the students, the researchers adopt the concept of experiential learning by Wolfe & Byrne with several adjusted phases, grouping, designing, conducting, transaction, final report, evaluation, and feedback. Thus, the results showed that the students gave positive feedback towards the e-commerce project and the students gained a lot of course achievements such as real business experience, the ability to operate e-commerce platforms, selling, promotion, marketing knowledge, and teamwork management since the e-commerce platform was employed in the Business English course. This research might be advantageous for enhancing and evaluating the running and the upcoming Business English course. Meanwhile, this project would be a fostering supplement for the students to grow their entrepreneurial spirit in the future.